Burkina Faso : The Zaï Technique and Enhanced Agricultural Productivity - World Bank (World Bank, Washington, DC, 2012)
More than 90 percent of the population in the Sahel lives on agriculture. The fact that crop production has not kept up with population growth during the last two decades is attributed to land degradation and productivity decline resulting in increased levels of rural poverty, food shortages and chronic food insecurity. In response, since the 1980s, Sahelian farmers have experimented with various soil and water conservation techniques to restore, maintain or improve soil fertility.